Careers and Emerging Opportunities in Visual Communication in Medicine: Medical photography in Norway - Kjersem, Bård (Journal of visual communication in medicine, 2015)
The community of medical photographers in Norway is relatively small. Except for one they are all employed with titles such as research technicians, department engineers, senior consultants and skilled workers. At the present there is no formal education in medical photography. The most common educational attainment for photographers is the Journeyman's certificate. Until recently, the requirement for employment for photographers at Norwegian hospitals was the Journeyman's Certificate. However, the Institutt for Klinisk Medisin at University in Oslo recently advertised a vacancy for a departmental Engineer to run its photographic and video services. The post required that the candidates possess either a Bachelor's degree in a relevant subject. This is the first vacancy in medical photography in nine years. The Norwegian health services have been reformed in the direction of New Public Management (NPM). To utilise the resources effectively, tasks that normally would be performed by one health profession are shifted to another with a different or lower education and training. There are reasons to believe that the shift of medical photography from professional photographers to other health personnel without specialist training or qualifications is an attempt to utilise resources more effectively. During the next two years a mixed methods research will be carried out to explore the current situation for medical photography in Norway.